Politics and Woman’s Career - Matonytė, Irmina (Sociologija. Mintis ir veiksmas, 2002)
On the basis of qualitative research (over 20 semistructured interviews) study concerning interrelations between women’s career and political environment, political-cultural norms as well as organizational situations and factors has been carried out. The main assumption is that career associates a person and the public sphere, reflects personal self-realization in society, community (career here is understood as personal trajectory to socially important positions in the decision making structure). Politics is analyzed through three axes. First, politics is a social game of legitimacy, influence, and authority. Second, politics is a concrete set of instruments (laws, regulations, unwritten rules, etc.) operating in a society in order to solve conflicts and to secure functioning of communal life. Third, politics is a structure of influences and value orientations in a close personal environment that is always vibrant, dynamic and open. Such politics means efforts, intentions and orientations of a concrete person to self-realize and to consolidate personal position in any concrete environment. In the present study life histories and stories of women from the middle class in the post-soviet Lithuania are being analyzed with an attempt to recognize how they operate in their environment and what are peculiar “feminine” political moves. Recommendations how it could be possible to change the existing situation into more career women favorable direction are provided at the end of the text.